The Authority of the Batam City Regional Government and the Batam City Free Trade and Free Port Authority in the Business Licensing Process Through the Online Single Submission Risk Based Approach Based on Legal Certainty - fetarina, Lisdwi; Widayati, Widayati (Jurnal Hukum Khaira Ummah, 2025)
The Unitary State of the Republic of Indonesia is a state based on law. This concept is stated in Article 1 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia which reads: The State of Indonesia is a state of law. The consequence of this article is that every action, whether it is the action of a citizen or the action of a state administrator (government), must be based on law and must not conflict with the applicable positive law (ius constitutum). The approach method used in this study is empirical juridical. According to Abdul Kadir Muhamad, empirical juridical research is: "research conducted by examining secondary data first and then continued by conducting research on primary data in the field". In legal research, law is seen as a norm or das sollen, because legal research is an approach that refers to applicable laws and regulations. The OSS RBA system created as a form of E-Government in Batam City aims to provide convenience to the public in accessing licensing documents on the OSS RBA system to issue permits independently through digital use and to facilitate officers in providing licensing services to the public. However, in the implementation of OSS RBA in Batam City so far, there have been various obstacles and problems that have caused the implementation of OSS RBA in Batam City as a system that helps the public issue licensing documents to not be implemented effectively enough. This study uses a descriptive qualitative approach to describe and analyze the implementation of OSS RBA in Batam City. Based on field data and literature review, several main findings were obtained